The Effect of Control Strength on Lag Synchronization of Nonlinear Coupled Complex Networks. (23rd May 2012) - Wang, Shuguo; Yao, Hongxing
Abstract : This paper mainly investigates the lag synchronization of nonlinear coupled complex networks using methods that are based on pinning control, where the weight configuration matrix is not necessarily symmetric or irreducible. We change the control strength into a parameter concerning time t, by using the Lyapunov direct method, some sufficient conditions of lag synchronization are obtained. To validate the proposed method, numerical simulation examples are provided to verify the correctness and effectiveness of the proposed scheme.